Revisiting the Relationship between Organisational Commitment and Professional Commitment: A Case Study of Academicians in a Private Educational Institution (Malaysian Management Journal, 2006)
Many studies have dwelled on various issues related to the concept of commitment. One particular issue concerns the relationship between organisational commitment and professional commitment. Between these foci of commitments, the issue has been whether both are compatible or in conflict with each other. The nature of the relationship between these variables is worth noting as it may have impact on the behaviour of individuals in organisations, and hence, the formulation and practice of human resource policies in these organisations. This paper reports the findings of a study conducted to investigate this issue of compatibility or conflict between the variables. The unit of analysis were academicians employed in a private research institution in Malaysia. The result of the mail survey revealed the existence of a commitment dilemma within the sample. No significant correlations were recorded between professional commitment and the various dimensions of organisational commitment. Additionally, professional commitment and organisational commitment correlated significantly with intent to stay in the profession and intent to stay with the organisation, respectively. Directions for further research were also discussed.